Mutation of zebrafish Snapc4 is associated with loss of the intrahepatic biliary network - Schaub, Madeline; Nussbaum, Justin; Verkade, Heather; Ober, Elke A.; Stainier, Didier Y. R.; Sakaguchi, Takuya F. (Developmental Biology, 2012)
Biliary epithelial cells line the intrahepatic biliary network, a complex three-dimensional network of conduits. The loss of differentiated biliary epithelial cells is the primary cause of many congenital liver diseases. We identified a zebrafish snapc4 (small nuclear RNA-activating complex polypeptide 4) mutant in which biliary epithelial cells initially differentiate but subsequently disappear. In these snapc4 mutant larvae, biliary epithelial cells undergo apoptosis, leading to degeneration of the intrahepatic biliary network. Consequently, in snapc4 mutant larvae, biliary transport of ingested fluorescent lipids to the gallbladder is blocked. Snapc4 is the largest subunit of a protein complex that regulates small nuclear RNA (snRNA) transcription. The snapc4s445 mutation causes a truncation of the C-terminus, thereby deleting the domain responsible for a specific interaction with Snapc2, a vertebrate specific subunit of the SNAP complex. This mutation leads to a hypomorphic phenotype, as only a subset of snRNA transcripts are quantitatively altered in snapc4s445 mutant larvae. snapc2 knockdown also disrupts the intrahepatic biliary network in a similar fashion as in snapc4s445 mutant larvae. These data indicate that the physical interaction between Snapc2 and Snapc4 is important for the expression of a subset of snRNAs and biliary epithelial cell survival in zebrafish. © 2011.
Created from Fastlane, Scopus look-up
Keywords: Biliary epithelial cells; Liver; SNAP190; SNAPC2; SnRNA; Vanishing bile duct